Cash holdings, capital structure and financial flexibility - Chua, Shen Hwee (2012)
This thesis is structured into two main parts to investigate the role of financial flexibility in firms’ liquidity and financing management. Financial flexibility is the most important practical determinant to managers when they make financing decisions. This missing link, financial flexibility, is identified by practitioners and used in this thesis to fill the missing gap between theory and practice in corporate finance. Part A of this thesis analyses the trends in firms’ internal financial flexibility and examines the role of this internal flexibility on investment behaviour of firms. Part B of this thesis then move on to examine the role of both internal and external financial flexibility on firms’ financing behaviour.